1995
DOI: 10.1143/jjap.34.973
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Ultrathin Dielectrics Grown by Microwave Afterglow Oxygen and N2O Plasma

Abstract: Ultrathin dielectrics, oxides and oxynitrides were grown using microwave afterglow oxygen and N2O plasma at low temperature. N2O plasma annealing and pretreatment improved the breakdown properties of O2 plasma oxides. From secondary ion mass spectroscopy (SIMS) analysis, nitrogen was found to be incorporated into oxides effectively by this low-temperature method. Nitrogen content was highest at the oxide surface and decreased toward the oxide/Si interface. This indicates a nitridation mechanism different fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

1996
1996
2010
2010

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 27 publications
1
9
0
Order By: Relevance
“…With N,0, nitrogen was incorporated throughout the 7-8-nm oxide layer, but the concentration was highest at the SiOj surface and decreased to the Si/SiO^ interface [79]. This distribution is similar to that observed in oxides thermally (furnace) nitrided with NH,.…”
Section: • Nitridation and Oxynitridation In Nfl And Njo^ Mixturessupporting
confidence: 69%
See 2 more Smart Citations
“…With N,0, nitrogen was incorporated throughout the 7-8-nm oxide layer, but the concentration was highest at the SiOj surface and decreased to the Si/SiO^ interface [79]. This distribution is similar to that observed in oxides thermally (furnace) nitrided with NH,.…”
Section: • Nitridation and Oxynitridation In Nfl And Njo^ Mixturessupporting
confidence: 69%
“…This distribution is similar to that observed in oxides thermally (furnace) nitrided with NH,. Nitrogen in the bulk oxide gave high tunneling currents, but MBDF ~8 MV/cm; the effective charge density was ~3 X lO' /cm , while the interface state density was >2 X 10''/cm'/eV [79].…”
Section: • Nitridation and Oxynitridation In Nfl And Njo^ Mixturesmentioning
confidence: 96%
See 1 more Smart Citation
“…Therefore, the tunneling thickness strongly influences the leakage current of the trapped charges from the storage layer through the tunneling layer. In addition, the thicker tunneling layer guarantees a continuous film and less defect density [16]. In this case, the retention properties of a device using the richest silicon storage layer can be improved by employing a thicker tunneling layer.…”
Section: The Electrical and Memory Properties Of The Ooxon Capacitorsmentioning
confidence: 99%
“…The NH 3 -nitrided oxides have a disadvantage of often having a large amount of electron traps induced by hydrogen inherent in NH 3 . [18][19][20][21] Masuda et al 17 reported the growth of ultrathin SiO 2 films by N 2 O plasma oxidation technique using a PECVD reactor. 16 In the case of direct oxynitridation in N 2 O or NO, the process temperature required is very high (1000°C to 1150°C), which makes the control of the oxynitride thickness, and nitrogen content and distribution in the bulk of the oxide and at the Si/SiO 2 interface more difficult.…”
Section: Introductionmentioning
confidence: 99%